Perception of Stigma among Caregivers of Mentally Ill People - Pandey, Srijana (Nepal Medical College Journal, 2019)
The lives of people with mental illness are altered by the symptoms of the illness, attitudes of people that view symptoms as threatening and uncomfortable, which foster stigma and discrimination within social circles. The catch of the study was to assess the stigmatizing beliefs among Caregivers of persons with mental illness. A descriptive and exploratory study was conducted with purposive sampling technique among 50 caregivers with interview method of mental illness patient with purposive sampling technique at Nepal Medical College teaching Hospital, Jorpati, Kathmandu, Nepal in Oct 2017- Nov 2017. The study revealed that the most of caregivers (62%) feel burdened financially, and about 64% think that people with mental illness are dangerous. Most of the caregivers (70%) think that the mentally ill people are violent. More than half (54%) of the caregivers think voluntary organizations are not doing adequate work in the field of mental health and 72%feel health organizations are giving less priority to mental illness as compared to other disorder. Most of the caregivers (66%) think that their occupational life has been interfered by the family member’s illness, and 56% don’t think that there are adequate law or rules regarding mental illness. In conclusion, care givers experience stigma such as concealment, negative experience, emotional stigma as well as work related stigma which affects the health and recovery of mentally ill persons. Compliance to medicine was poor and relapse rate was high which also have impact on the life of caregiver.